Fabrication of electrochemically reduced grapheme oxide composite based electrochemical sensor for the detection of 3-nitrophenol - Muhammad, Nafiu (2015)
In this research electrochemical sensor for the detection of 3-nitrophenol has been successfully developed based on electro-reduced graphene oxide (ERGO) functionalized with cyltrimethylammonium bromide (CTAB) and electro-reduced graphene oxide functionalized with poly(3,4-ethylenedioxythiophene) (PEDOT) on screen printed carbon electrode (SPCE). Two methods of preparations were used. Firstly, graphene oxide-CTAB was dropped cast onto the SPCE and later reduced using cyclic voltammetry technique to produce ERGO/CTAB. Secondly, ERGO/PEDOT was prepared by direct electrodeposition of mixture containing EDOT/GO in LiClO4 to produce PEDOT/ERGO on SPCE. The modified SPCE were characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), Raman spectroscopy, scanning electron microscope (SEM) and energy dispersive X-ray (EDX), respectively. Their electrochemical activities and sensing capability towards 3-nitrophenol was investigated using linear sweep voltammetry (LSV). The modified SPCEs showed a remarkable activity which attributed to the excellent conductivity, large surface area, electrocatalytic activity and good synergistic effect of the nanocomposite films toward 3-nitrophenol. To increase the sensitivity of the developed sensors experimental parameters such as pH buffer, scan rate, accumulation time and potential were optimized. Under the optimum experimental conditions, the ERGO/CTAB developed sensor displays two linear calibration curve in the concentration range of 0.5 and 100 μM with linear regression coefficients R2 = 0.9915 and 0.9972 and detection limit of 0.04 μM. While PEDOT/ERGO modified SPCE gave linear calibration curve in the concentration range from 0.3 to 70 μM with linear regression equation y = 5.0042C (μM) + 45.674, R2 = 0.9934 and detection limit of 0.08 μM. The proposed methods showed good selectivity of target analyte even in the presence of some foreign ions. A good reproducibility was recorded with RSD of 4.71% for ERGO/CTAB and 3.85 % for PEDOT/ERGO, respectively.